Influence of time-of-day-specific same-session combined endurance and strength training on maximal and submaximal endurance parameters - Vuong, Minh Kiet (2015)
Endurance and strength training are often performed concurrently by both elite athletes and recreational individuals. The question of whether the order of exercises or training at certain daytimes yields to different adaptations in endurance and strength parameters, when endurance and strength training are combined into a single training session, has received limited scientific attention. Moreover, effects on cardiorespiratory and neuromuscular variables after same-session concurrent training have shown conflicting results, particularly regarding exercise sequence or time-of-day characteristics. The purpose of the present study was to examine the effect of time-of-day-specific same- session combined endurance and strength training on maximal and submaximal endurance parameters.